Pengaruh Optimisme, Prokrastinasi Akademik, Motivasi Belajar, Efikasi Diri, dan Dukungan Sosial Terhadap Tingkat Stres Akademik Mahasiswa Kota Surabaya - Desy Kartika Sari; Hwihanus (Jurnal Riset Multidisiplin Edukasi, 2025)
This study examines the influence of Optimism, Academic Procrastination, Learning Motivation, Self-Efficacy, and Social Support on Academic Stress Levels in Surabaya City students using quantitative methods and a cross-sectional design. The research sample used was 53 respondents, selected using the Non-Probability Convenience Sampling technique. Respondents filled out a Google Form questionnaire based on a 5-point Likert scale. Data analysis was performed using Partial Least Squares–SEM in SmartPLS software with outer and inner model evaluation and bootstrapping procedures. The results of the hypothesis test showed only two significant direct relationships: Optimism had a positive and significant effect on Self-Efficacy (β = 0.306; p = 0.036), and Self-Efficacy had a positive and significant effect on Academic Stress Levels (β = 0.545; p = 0.008). Other hypotheses, including the direct effects of Academic Procrastination and Learning Motivation on Self-Efficacy and Academic Stress Levels, and the moderating role of Social Support, were not proven significant. Testing of the mediation path also did not find a significant indirect effect through Self-Efficacy. These findings suggest that interventions to reduce academic stress need to consider the context of academic demands and strengthen contextualized coping strategies; increased optimism can strengthen efficacy, but higher efficacy in this sample was associated with greater stress levels, necessitating a balanced approach between strengthening self-efficacy and managing academic workload.